(untitled) (Annals of Medical Research, 2021)
Aim: This study aims to investigate the relationship between Idiopathic Carpal Tunnel Syndrome (CTS) and Vitamin D Level, Body Mass Index (BMI), and Fasting Blood Sugar.Materials and Methods: 54 CTS patients diagnosed electrophysiologically were included in the study. These patients’ ages, genders, height and body weights, and body mass index values were recorded. Laboratory tests including vitamin D levels and fasting blood sugars were performed for each participant. The CTS stage was determined electrophysiologically and the Boston questionnaire and the visual analogue scale (VAS) were filled to assess total pain scores, symptom severities (CNS), and functional states (FSS).Results: There was a statistically significant difference between the distribution of CTS stages in female patients and male patients (p = 0.008). There was no statistically significant difference between mild, moderate, and severe CTS stages in terms of age, body mass index, and fasting blood glucose (p = 0.459; p = 0.232; p = 0.413, respectively). There is a statistically significant difference between CTS stages in terms of vitamin D levels (p0.001). Vitamin D averages were observed to decline from mild to severe stages of CTS. According to the Boston Carpal Tunnel Syndrome functional status scale, it was determined that there is marginal statistical significance between the stages of CTS. It was observed that the mean functional status scale scores increased from the mild stage to the severe stage (p = 0.055). There was no statistically significant difference between mild, moderate, and severe CTS stages in terms of VAS pain and paresthesia scores and the Boston Carpal Tunnel Syndrome symptom severity scale (p = 0.340; p = 0.359; p = 0.250, respectively).Conclusion: We found a significant relationship between the vitamin D level and the CTS stage. According to Boston Carpal Tunnel Syndrome Questionnaire, we found that there is a marginal statistical significance between the stages of CTS.